Characterization of PCN emission and removal from secondary copper metallurgical processes. (March 2020) - Dat, Nguyen Duy; Huang, Yong Ji; Chang, Moo Been
Abstract: This study investigates the characteristics of PCN emission and removal from two secondary copper metallurgical processes (plants A and B) equipped with different air pollution control devices (APCDs). Different operating conditions and feeding materials result in varying emission factors of PCNs from two plants. The average PCN concentration emitted from plant B (7597 ng Nm −3 ) is significantly higher than that emitted from plant A (32.5 ng Nm −3 ) and those reported in China (5.8–2845 ng Nm −3 ). Similar trend is found for fly ash samples collected from two plants. Low chlorinated homologues (Mono-to Tri-CNs) are the major contributors to total PCNs measured in flue gas, fly ash and slag samples. Combination of semi-dry absorber, activated carbon injection and baghouse is effective for PCN removal in plant A, with the overall removal efficiency of 98%. The overall removal efficiency of PCNs achieved with APCDs equipped in plant B is 90%, however, increases of some homologues as the flue gases passing through baghouse and wet scrubber are found, suggesting the occurrence of memory effect within baghouse and wet scrubber. Graphical abstract: Image 1 Highlights: Significantly higher PCNs concentration is emitted from plant B compared to plant A. PCNs are effectively removed by semi-dry absorber, AC injection and baghouse. Memory effect occurs in baghouse and wet scrubber. Low chlorinated homologues are major contributors to total PCNs emitted. Abstract : This study investigated the characteristics of PCNs emitted from two secondary copper metallurgical processes. Results indicate high emission factors of PCNs and appropriate combination of air pollution control devices for effective PCN removal is needed for reducing PCNs emission from secondary copper smelting process.